PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA PEMBELAJARAN MENGIDENTIFIKASI JENIS MAKANAN HEWAN DI SD - Sukaesih, Ocih (Universitas Pendidikan Indonesia, 2015)
Class IV Elementary School students Jatiroke I Jatinangor Sumedang Regency difficulties inÂ completing the learning to identify the type of pet food in learning science. Efforts are being made to overcome this problem is to use cooperative learning model Students Teams Achievement Divisions (STAD) through classroom action research. Based on the research results, in cycle 1 has been a significant increase in learning to identify the type of pet food, namely the acquisition value of 18 students who scored in the top 70 increased to 10 students or 55%. In cycle 2, all students or 100% of students scored in the top 70.Keywords: learning, cooperative, STAD, IPA, animals.